An outbreak of skin disease (alopecia) associated with high mortality in Menz lambs in Ethiopia - Tibbo, Markos; Bayou, K.; Mekonnen, S.; Abdicho, S.; Woldemeskel, M. (2005)
Aetiological investigation was made into an outbreak of skin disease (alopecia) in 216 Menz weaner lambs in Ethiopia, through clinical, laboratory and post mortem examinations. Morbidity, mortality and case fatality rates were 84.7%, 50.5% and 59.6%, respectively. The clinical signs included symmetrical wool loss from mid-line dorsum extending laterally and ventrally with hair picking. Emaciation and dehydration were observed with significantly higher (P<0.001) PCV and MCV, and lower (P<0.05) WBC levels in affected than in unaffected lambs. There was a complete to partial loss of wool with a history of exfoliation of the skin. Superficial and easily removable horny scales, which later disappeared after the complete wool loss in some and developed into exudative dermatitis in others, were seen. In the abomasum, trichobezoars of various sizes were found blocking the pylorus. The skin was hyperkeratotic with atrophy of the epidermal layer and thickened oedematous dermis. Mineral deficiency and changes in serum enzyme levels were not significant enough to indicate the clinical disease. Moreover, mineral supplementation did not improve the incidence of alopecia and death. The findings were suggestive of possible endocrine disturbance. The outbreak in this study could be attributed to genetic predisposition believed to be the cause in these Menz lambs under genetic selection.